A Multi-Tiered Cloud-Based Framework for Automated Quality Documentation Management in Higher Education - Alharbi, Mohammed Hussain; Zayani, Hafedh Mahmoud (Engineering, Technology & Applied Science Research, 2026)
The systematic management of quality assurance documentation is a cornerstone of institutional accreditation. This paper presents an integrated automated framework developed for Northern Border University (NBU) using Microsoft Excel 365 and OneDrive. The system manages the full lifecycle of 13 core quality tasks—including Program Reports, Course Portfolios, and Program Learning Outcome Assessment Reports—across 10 colleges and 56 academic programs (39 Bachelor's and 17 Master's). The framework employs a three-tier governance architecture that synchronizes workflows across the Academic Program, College Quality Unit, and University Deanship using low-code cloud automation. Results from university-wide deployment show that the institutional compliance ratio improved from a baseline of 0.49 to 0.96. The implementation achieved a 75% reduction in administrative man-hours, saving over 500 hours per cycle, whereas the average delay for critical submissions such as the Program Report was reduced from 18 days to just 4 days. Furthermore, 100% verification of Department and College Council minutes was achieved, demonstrating a scalable and platform-agnostic model for sustainable institutional governance.